Penegakan Sanksi Disiplin Berat terhadap Pegawai Negeri Sipil di Lingkungan Kementerian Perhubungan - Ahmad Muhid Estiyanto (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
This study is a non-dogmatic study or empirical study, where law is the embodiment of the symbolic meanings of social actors which are seen in the interactions between them. The aim of the research is to find out the procedures for applying heavy disciplinary sanctions to civil servants in accordance with Government Regulation Number 94 of 2021 and to find out the application of heavy disciplinary sanctions to civil servants within the Ministry of Transportation. Based on Government Regulation Number 94 of 2021 concerning Civil Servant Discipline, severe disciplinary penalties are divided into three categories: First, demotion to a lower level position for 12 months, Second, release from position to acting position for 12 months, and Third, honorable dismissal not at his own request as a Civil Servant. The procedures for imposing heavy disciplinary sanctions are contained in BKN Regulation Number 6 of 2020, which includes: forming an inspection team, summons, examination, determining heavy disciplinary penalties and delivering decisions on heavy disciplinary penalties. The research results show that the Ministry of Transportation has implemented severe disciplinary sanctions in accordance with applicable regulations, namely Government Regulation Number 94 of 2021 concerning Civil Servant Discipline. The Ministry of Transportation has also implemented the stages that have been mandated in the legal regulations that serve as guidelines for its implementation, namely State Civil Service Agency Regulation Number 6 of 2022. The factors that hinder the implementation of heavy disciplinary sanctions include officials suspected of committing serious disciplinary violations, not being temporarily released. from his position, the immediate superior has not played an active role in handling disciplinary violations, Submitting Decrees on Severe Disciplinary Punishments which do not comply with the provisions.